SASCI-Mayo Clinic Fellows webinar: Managing bleeding complications in acute coronary syndrome - Weich, H; Mazaza, A; Gharacholou, SS; Barsness, GW; Khan, S; Holmes, D (SA Heart Journal, 2025)
Education remains a core purpose of the South African Society of Cardiovascular Intervention (SASCI), with an emphasis on engaging cardiology fellows in training through regular, structured educational initiatives. In support of this mission, SASCI has partnered with two of our past "Visiting Professors", David Holmes and Gregory Barsness of the Mayo Clinic in Rochester Minnesota, to host quarterly, case-based Fellows Webinars. The webinars are designed to foster critical thinking and clinical decision-making through interactive, case-based discussions and have thus far been very well received, with an average of 70 participants across Southern Africa and beyond. Specific topics are selected by the SASCI faculty in collaboration with the Mayo cardiologists. Each webinar session has a structured agenda, starting with a clinical case presentation by a cardiology fellow. This is followed by a concise, focused lecture by a Mayo Clinic expert, to provide context and evidence-based guidance. A robust discussion then follows, moderated jointly by the SASCI and Mayo faculty, where active participation by fellows is encouraged. The session concludes with the case presenter sharing a brief follow-up, detailing patient outcomes and the rationale behind management decisions. All cases are anonymised to protect patient confidentiality. Each webinar is recorded and made available online at https://form.jotform.com/251685088627570. Access is restricted to verified healthcare professionals. In line with our commitment to ongoing academic contribution, each webinar is intended to culminate in a peer-reviewed manuscript for publication in the South African Heart Journal. As part of the webinar series, the current manuscript focuses on uncommon bleeding complications in patients with acute coronary syndromes, a clinically relevant yet often underappreciated challenge in contemporary interventional cardiology.